A priori estimate and existence of solutions with symmetric derivatives for a third-order two-point boundary value problem - Smirnov, Sergey (Mathematical Modelling and Analysis, 2025)
We study a priori estimate, existence, and uniqueness of solutions with symmetric derivatives for a third-order boundary value problem. The main tool in the proof of our existence result is Leray-Schauder continuation principle. Two examples are included to illustrate the applicability of the results.